2002
DOI: 10.1128/aac.46.12.3724-3730.2002
|View full text |Cite
|
Sign up to set email alerts
|

Target Site Concentrations of Ciprofloxacin after Single Intravenous and Oral Doses

Abstract: To characterize the potential of ciprofloxacin penetration into human soft tissues following intravenous (i.v.) and oral (p.o.) administration, we measured the free ciprofloxacin concentrations in interstitial space fluid of skeletal muscle and subcutaneous adipose tissue by microdialysis. In addition, ciprofloxacin concentrations were measured in cantharis-induced skin blisters, saliva, and capillary plasma and were compared to the total concentrations in venous plasma. The concentrations in saliva and capill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 21 publications
4
61
0
1
Order By: Relevance
“…The availability of ciprofloxacin at the interstitial target site is considered to be an important determinant for the effectiveness of antimicrobial therapy and to be the clinical outcome of an infection. In a study, concentrations in the interstitial fluid space at the target sites and AUCs were significantly lower than the corresponding concentrations in plasma for dosages of 400 and 500 mg 91 .…”
Section: Distributionmentioning
confidence: 99%
“…The availability of ciprofloxacin at the interstitial target site is considered to be an important determinant for the effectiveness of antimicrobial therapy and to be the clinical outcome of an infection. In a study, concentrations in the interstitial fluid space at the target sites and AUCs were significantly lower than the corresponding concentrations in plasma for dosages of 400 and 500 mg 91 .…”
Section: Distributionmentioning
confidence: 99%
“…However, there are also examples in the literature that suggest method-specific differences in determined free drug concentrations. For example, it was shown that following oral administration, ciprofloxacin penetrates preferentially into inflamed lesions, such as cantharis-induced skin blisters (area under the concentration-time curve for blister fluid [AUC blister ]/ AUC plasma ϭ 1.44 Ϯ 0.16), a fact that would have been missed based on measurements from different sampling sites, such as saliva (AUC saliva /AUC plasma ϭ 0.33 Ϯ 0.01) or capillary blood (AUC capillary blood /AUC plasma ϭ 0.88 Ϯ 0.07) (90).…”
Section: Target Site Exposurementioning
confidence: 99%
“…In addition, many systemically administered drugs distribute into the skin, with local exposure approaching (Klimowicz et al, 1988;Borg et al, 1999;Krishna et al, 2010), or sometimes even exceeding, corresponding plasma levels (Zucchi et al, 2001;Brunner et al, 2002). As a result, cutaneous drug metabolism is relevant for pharmacotherapy, both from the perspectives of metabolic elimination and activation of prodrugs, as well as the formation of reactive metabolites that may cause skin toxicity (Sharma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%